Characteristics of Low‐Frequency Pulses Associated With Downward Terrestrial Gamma‐Ray Flashes. Issue 5 (5th March 2022) - Wada, Y.; Morimoto, T.; Nakamura, Y.; Wu, T.; Enoto, T.; Nakazawa, K.; Ushio, T.; Yuasa, T.; Tsuchiya, H.
Abstract: Winter thunderstorms in Japan have been recognized as an ideal target to observe high‐energy atmospheric phenomena thanks to low‐charge‐center cloud structures. During four winter seasons in Japan (from 2016 October to 2020 March), seven downward terrestrial gamma‐ray flashes (TGFs) were detected by gamma‐ray and broadband low‐frequency (LF: 0.8–500 kHz) monitors. All the detected TGFs took place at the initial stage of lightning flashes. Based on the LF observation, the seven downward TGFs in the present study can be classified into two types: energetic‐bipolar and small‐bipolar types. Three of them are energetic‐bipolar events, coincident with a high peak‐current LF pulse that originates from a negative return stroke with a peak current larger than 100 kA. The others are small‐bipolar events, followed by a negative bipolar LF pulse with a moderate peak current. Three of the four small‐bipolar events are multi‐pulse TGFs, while all of the energetic‐bipolar events in this study are single‐pulse TGFs. Plain Language Summary: Terrestrial gamma‐ray flashes (TGFs) are a transient high‐energy emission from lightning discharges. While a lot of upward TGFs have been detected by satellites, a few downward TGF have been detected by ground‐based experiments. Our detection network in Japan has detected seven downward TGFs in winter thunderstorms for 4 years. Lightning discharges associated with the downward TGFs were also monitored in the low‐frequency radio band. The low‐frequency pulses associated with the downward TGFs can be classified into two types. Correlation analysis of downward TGFs with gamma‐ray and low‐frequency observations is a powerful approach to reveal the production mechanism of TGFs. Key Points: Downward terrestrial gamma‐ray flashes (TGFs) in winter thunderstorms of Japan can be classified into two types based on low‐frequency (LF) observations Three events were single‐pulse TGFs coincident with high peak‐current LF pulses of return strokes Four events were followed by moderate peak‐current LF pulses, and three of them are multi‐pulse TGFs